A non-parametric approach to testing the axioms of the shapely value with limited data - Victor Aguiar; Roland Pongrou; Jean-Baptiste Tondji (The University of Western Ontario, Department of Economics, 2017)
The unique properties of the Shapley value-efficiency, equal treatment of identical input factors, and marginalityhave made it an appealing solution concept in various classes of problems. It is however recognized that the pay schemes utilized in many real-life situations generally depart from this value. We propose a nonparametric approach to testing the empirical content of this concept with limited datasets. We introduce the Shapley distance, which, for a fixed monotone transferable-utility game, measures the distance of an arbitrary pay profile to the Shapley pay profile, and show that it is additively decomposable into the violations of the classical Shapley axioms. The analysis has several applications. In particular, it can be used to assess the extent to which an income distribution or a cost allocation can be considered fair or unfair, and whether any particular case of unfairness is due to the violation of one or a combination of the Shapley axioms.
Keywords: C71; C78; D20; D30; J30; 330; Shapley value; fairness violations; limited data; inequality